EFEK DURASI PENGGUNAAN MASKER KAIN TERHADAP END-TIDAL KARBON DIOKSIDA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA - Razana Awan; Bertha J. Que; Ony W. Angkejaya; Felmi de Lima (PAMERI, 2022)
Cloth masks serve to protect users from particles carried through droplets, or airborne. The use of cloth masks for a longer period of time can cause hypercapnia with symptoms such as dyspnea, tachycardia, dizziness, and headaches, which are characterized by CO2 levels >45. This research method is an experimental method, with a simple random sampling technique, with 36 respondents divided into two groups, namely control and treatment. Observational data were analyzed using the Independent Sample T-Test if the data was normally distributed and Mann-Whitney if the distribution was not normal. The results of the Mann-Whitney test showed that at minute 0 the p value = 0.864, the results of the Independent Sample T-Test test at minute 30 the control group p value = 0.850, the treatment group p value = 0.851 minutes to -60 control group p value = 0,935, treatment p value = 0,935, 90th minute control group p value = 0,568, treatment group p value = 0,569 minute 120 control group p value = 0,056, treatment group p value = 0,056. From the results of the five measurements, the average p value = > 0.05, which means there is no significant difference. The test results mean that there is no effect between the duration of using a cloth mask on the end-tidal carbon dioxide.